Gender and the Performance of Death Rituals in Classical Athens 480–332 BCE - Salem, Radwa (Religion & gender, 2024)
Death rituals play a significant role in maintaining the cultural system of different societies by providing a specific form of behaviour in response to death. To that end, the significant role of women as patrons of culture can be identified by studying their role in the performance of death rituals. Classical Athens provides a good case study as women performed most phases of the mortuary treatment, and their role is recognised in both the textual and material evidence. This gives us the opportunity to diverge from the ‘typical male perspective’-approach to the mortuary evidence, which focuses on the socio-political and economic dimensions, and shed light on the agency of women. The female agency was responsible for the continuity of some ancient rituals despite the laws made to restrict them. Moreover, relatively wealthier women were indirect agents influencing the Athenian public life by using excessive death rituals to reallocate power in society after the loss of powerful individuals.